Generar un producto audiovisual, para potenciar las bandas de pueblo como patrimonio sonoro en la ciudad de pasaje. - Fárez Pereira, Marco Vinicio (2017)
Pasaje, for years has been considered a city of high musical and festive consumption within the province and the country, in this sense the village bands become local sound patrimony, so there are conditions and support to develop an audio visual product In which it promotes the culture of the bands of people, sustained and based on a previous investigation through interviews, surveys, conversations of the inhabitants and people understood in the subject, It will deepen in the investigation of the theoretical axes with the purpose of extending the Conceptual scope of the elements that are involved in the object of study, then the research instruments will be designed, whose data will be processed in tabulation tables. The data and elements obtained will be interpreted to identify the factors inherent to the audiovisual product to be realized.